20th AIAA/CEAS Aeroacoustics Conference 2014
DOI: 10.2514/6.2014-3354
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation and analytical modeling of locally reacting, single degree of freedom acoustic liners with turbulent grazing flow

Abstract: Single degree-of-freedom conventional acoustic liners are widely installed in jet engines to reduce internal engine noise. They work by converting acoustic energy into vorticity-bound fluctuations. Despite being widely used, effective design-stage models of acoustic liners placed in high sound amplitude conditions, possibly with a turbulent grazing flow, are not available due to the near-liner flow complexity and diagnostic challenges. The work presented in this thesis uses direct numerical simulations (DNS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…[41,42] Using DNS to solve all characteristics of the flow is the most accurate option, however it requires an intensive computational resource. [11] 3D large-eddy simulation (LES) represents an alternative to DNS, in which small sub-grid scales (SGS) structures are modelled and the large-scale ones are resolved through application of a filtering procedure. [43,44] This filtering reduces the computational complexity, such that the high frequencies are removed from the solutions, but their effects on the resolved scales are still taken into account.…”
Section: Methods Of Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…[41,42] Using DNS to solve all characteristics of the flow is the most accurate option, however it requires an intensive computational resource. [11] 3D large-eddy simulation (LES) represents an alternative to DNS, in which small sub-grid scales (SGS) structures are modelled and the large-scale ones are resolved through application of a filtering procedure. [43,44] This filtering reduces the computational complexity, such that the high frequencies are removed from the solutions, but their effects on the resolved scales are still taken into account.…”
Section: Methods Of Investigationmentioning
confidence: 99%
“…With increased SPL the structure of the vortices within the shear layer over the orifice is also altered and dissipated more quickly. Using direct numerical simulations (DNS), Zhang et al [10,11]) also analysed the velocity and pressure fluctuations within a Helmholtz resonator in the presence of a grazing flow and an acoustic field. It was concluded that when the grazing flow is laminar the fluctuations within the resonator cavity are limited, while the turbulent boundary layer produces more interactions.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, their numerical and experimental studies 13 of eight slit resonators with grazing flow have been carried out and self-noise has been detected. Zhang and Bodony 14,15 considered 3D hexagonal resonator in calculation with normal incident acoustic wave, and they [16][17][18] have continuously working on 2D and 3D numerical investigation on resonator with grazing flow, which provides detailed flow field revealing the complex interaction between boundary layer and the orifice. These numerical simulations show great advantage in reproducing complex phenomena around resonator slit or orifice.…”
Section: Introductionmentioning
confidence: 99%